Thermal smoke back-layering flow length with ceiling extraction at upstream side of fire source in a longitudinal ventilated tunnel. (5th August 2016) - Tang, F.; Li, L.J.; Mei, F.Z.; Dong, M.S.
Highlights: Thermal smoke back-layering flow length was investigated in a 72 m long model tunnel. The coupling effect of ceiling point extraction and longitudinal ventilation are considered. Ceiling extraction at upstream side of fire source was studied. A new non-dimensional factor was proposed to predict the smoke back-layering flow length. Abstract: This paper investigates experimentally the thermal buoyant smoke back-layering flow length beneath the tunnel ceiling with combination ceiling extraction and longitudinal ventilation, especially focusing on the condition that the ceiling extraction is employed at upstream side of the fire source, which has not previously been reported. Experiments are conducted in a model tunnel. A square gas burner was used to simulate the fire source, whose side dimension is 0.3 m. The heat release rates (HRRs) of fire source were 30 kW, 40 kW and 50 kW. Ceiling extraction opening with circular outlet of 0.3 m diameter was located at 1 m upstream from the fire source. Six different longitudinal ventilation velocities with six different ceiling extraction flow velocity were considered. Thermocouples are employed to measure the longitudinal temperature profile of the thermal smoke flow beneath the tunnel ceiling, to determine the upstream back-layering flow length. It was found that the upstream back-layering flow length increases with increase in heat release rate, meanwhile decreases with increase in longitudinal ventilation velocity or ceiling extraction velocity. A new non-dimensional factor was proposed to predict the thermal smoke back-layering flow length, which is shown to be in good agreement with the experimental results.